Beyond barriers fresh frontiers: selected readings on languages, literatures, and cultures - Talif, Rosli (Universiti Putra Malaysia Press, 2005)
The 20 articles in this volume are from the Malaysia International Conference on Languages, Literature and Culture 2003, which was organised by Universiti Putra Malaysia. They offer fresh perspectives on several themes, including: the determinants of how language is acquired; the usage and communication roles of language; the enactments of power in post-colonial literature; and language in inter-cultural cross-communication. Two of the papers are on Malaysia; one discusses language choice in the Malaysian legal context, and the other argues for a more proactive approach towards Malaysian research in corpus linguistics.